2006
DOI: 10.5650/jos.55.593
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Placebo-Controlled Study of Effects of Plant Sterol Enriched Vegetable Juice on Serum Cholesterol Concentrations in Mildly Hypercholesterolemic Subjects and Safety Evaluation

Abstract: A double-blind, placebo-controlled study was carried out to determine the effective dosage of a vegetable and fruit juice mix, enriched with free plant sterol (sterol VFJ), on serum concentrations of cholesterol and safety assessment was made for normocholesterolemic and mildly hypercholesterolemic Japanese subjects as high dosage (HG: 1.6 g sterol/day), low dosage (LG: 0.8 g sterol/day) and placebo control groups (CG). All subjects were continuously monitored during a 12-week treatment period and serum choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Forty‐seven studies had a single‐arm parallel group whereas 32 studies had a crossover design (Abumweis et al, ; de Graaf et al, ; De Smet et al, ; Demonty, Chan, Pelled, & Jones, ; Esther et al, ; Farquhar & Sokolow, ; Fuentes et al, ; Hallikainen et al, ; Hendriks, Weststrate, Van Vliet, & Meijer, ; Ho, Liu, & Loke, ; Jones, Vanstone, Raeini‐Sarjaz, & St‐Onge, ; Kassis, Vanstone, Abumweis, & Jones, ; Naumann, Plat, & Mensink, ; Neil, Meijer, & Roe, ; Ottestad et al, ; Plat et al, ; Plat & Mensink, ; Theuwissen & Mensink, ; Thomsen, Hansen, Christiansen, Green, & Berger, ; Volpe et al, ). Included studies were carried out in patient with dyslipidemia (Varady et al, ; Ottestad et al, ; Gylling, Hallikainen, Nissinen, & Miettinen, ; Bañuls et al, ; Hironaka, Shioya, Matsubara, Matsuoka, & Itakura, ; Sukmaniah et al, ; Becker et al, ; Stelmach‐Mardas et al, ; Furuncuoğlu, Başar, Alici, & Şengül, ; Abumweis et al, ; Cabezas, De Vries, Van Oostrom, Iestra, & Van Staveren, ; de Graaf et al, 2002; De Jong et al, ; Demonty et al, ; Fuentes et al, ; Gylling et al, ; Hallikainen, Kurl, Laakso, Miettinen, & Gylling, ; Hallikainen, Sarkkinen, Gylling, Erkkilä, & Uusitupa, ; Hallikainen & Uusitupa, ; Hendriks et al, ; Hsu et al, ; Jones et al, ; Jones et al, ; Kassis et al, ; Korpela et al, ; Lestiani et al, ; Matvienko et al, ; Neil et al, ; Plat & Mensink, ; Plat et al, ; Smet, Mensink, & Plat, ; Solà et al, ; Theuwissen and Mensink, 2007; Thomsen et al, ; Volpe et al, ; Woodgate, Chan, & Conquer, ), diabetes (Gao et al, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty‐seven studies had a single‐arm parallel group whereas 32 studies had a crossover design (Abumweis et al, ; de Graaf et al, ; De Smet et al, ; Demonty, Chan, Pelled, & Jones, ; Esther et al, ; Farquhar & Sokolow, ; Fuentes et al, ; Hallikainen et al, ; Hendriks, Weststrate, Van Vliet, & Meijer, ; Ho, Liu, & Loke, ; Jones, Vanstone, Raeini‐Sarjaz, & St‐Onge, ; Kassis, Vanstone, Abumweis, & Jones, ; Naumann, Plat, & Mensink, ; Neil, Meijer, & Roe, ; Ottestad et al, ; Plat et al, ; Plat & Mensink, ; Theuwissen & Mensink, ; Thomsen, Hansen, Christiansen, Green, & Berger, ; Volpe et al, ). Included studies were carried out in patient with dyslipidemia (Varady et al, ; Ottestad et al, ; Gylling, Hallikainen, Nissinen, & Miettinen, ; Bañuls et al, ; Hironaka, Shioya, Matsubara, Matsuoka, & Itakura, ; Sukmaniah et al, ; Becker et al, ; Stelmach‐Mardas et al, ; Furuncuoğlu, Başar, Alici, & Şengül, ; Abumweis et al, ; Cabezas, De Vries, Van Oostrom, Iestra, & Van Staveren, ; de Graaf et al, 2002; De Jong et al, ; Demonty et al, ; Fuentes et al, ; Gylling et al, ; Hallikainen, Kurl, Laakso, Miettinen, & Gylling, ; Hallikainen, Sarkkinen, Gylling, Erkkilä, & Uusitupa, ; Hallikainen & Uusitupa, ; Hendriks et al, ; Hsu et al, ; Jones et al, ; Jones et al, ; Kassis et al, ; Korpela et al, ; Lestiani et al, ; Matvienko et al, ; Neil et al, ; Plat & Mensink, ; Plat et al, ; Smet, Mensink, & Plat, ; Solà et al, ; Theuwissen and Mensink, 2007; Thomsen et al, ; Volpe et al, ; Woodgate, Chan, & Conquer, ), diabetes (Gao et al, …”
Section: Resultsmentioning
confidence: 99%
“…We concluded that PS supplementation was not able to affect percentage fat mass and WC in comparison with placebo consumption. However, the number of studies that assessed these effects was low, and these studies were very similar in terms of applied dosages and the duration of intervention periods (Cheung et al, ; De Smet et al, ; Hironaka et al, ; Hongu et al, ; Sialvera et al, ; Sukmaniah et al, ; Varady et al, ). Further studies that will apply different doses and duration of the interventions are needed to elucidate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen studies reported the effect of Phytosterol supplementation on liver function. Among the included studies one study, used two doses of Phytosterol (Hironaka et al , 2006) and two used three doses (Kurokawa et al , 2008; Davidson et al , 2001)and we considered as separate studies. These studies were published between 1996 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of studies were from the Asian populations (Hironaka et al , 2006; Hsu et al , 2017; Javanmardi et al , 2018b; Kriengsinyos et al , 2015; Ishizaki et al , 2003; Matsuoka et al , 2004; Seki et al , 2003; Kurokawa et al , 2008; Takeshita et al , 2007), three from American populations (Davidson et al , 2001), and three from European populations (Gylling et al , 2010; Richter et al , 1996). The duration of intervention ranged from 4 to 52 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Hironaka et al reported that plant sterol-enriched vegetable juice reduced serum total and LDL-cholesterol concentrations in Japanese subjects 20) . These reports suggest that the cholesterol-lowering activity of free plant sterols was maintained in a water-rich condition.…”
Section: Discussionmentioning
confidence: 99%